Mechanism testing of the empowerment of green transformation and upgrading of industry by the digital economy in China - Liu, Jiang; Zhao, Qianyu (Frontiers in Environmental Science, 2024)
With the continuous advancement of industrialization, global environmental problems are becoming increasingly severe. Maintaining economic growth while improving environment has been an important issue for many countries, especially developing countries. As industry is a major source of environmental pollution, industrial green transformation and upgrading has become particularly important. In the era of the digital economy, there is a new path for industrial green transformation and upgrading. Based on provincial industrial data from 2008 to 2021, a DID model was constructed to analyse positive environmental and economic benefits. New paths are provided for trade-offs between environmental improvement and economic growth in China. And new ideas are provided for global environmental issues and economic issues in the digital economy. The present study found that the digital economy has reduced the intensity of pollution emissions and elevated TFP, which has helped promote industrial green transformation and upgrading. Further mechanism testing showed that the digital economy has promoted industrial green transformation and upgrading by improving the utilisation of energy and resources and promoting technological innovation. Considering the utilisation of energy and resources, the digital economy has decreased China's total industrial energy and coal consumption, reduced industrial water consumption, reduced the share of coal consumption in China's total industrial energy consumption, and increased the share of clean energy consumption in China's total industrial energy consumption, which has optimised the efficiency and structure of China's energy utilisation to contribute to a green transformation and the upgrading of industry. In technological innovation, the development of the digital economy has increased industrial innovation output and R&D input. Further, it has promoted green process innovation, accelerating technological innovation and realised industrial green transformation and upgrading.